The influence of partnership on contraceptive use among HIV-infected women accessing antiretroviral therapy in rural Uganda - Nieves, Christina I.; Kaida, Angela; III, George R. Seage; Kabakyenga, Jerome; Muyindike, Winnie; Boum, Yap; Mocello, A. Rain; Martin, Jeffrey N.; Hunte, Peter W.; Haberer, Jessica E.; Bangsberg, David R.; Matthews, Lynn T. (Contraception, 2015)
Objective: The objective was to determine individual and dyadic factors associated with effective contraceptive use among human immunodeficiency virus (HIV)-infected women accessing antiretroviral therapy (ART) in rural Uganda. Study design: HIV-infected women enrolled in the Uganda AIDS Rural Treatment Outcomes cohort completed questionnaires (detailing socio-behavioral characteristics, sexual and reproductive history, contraceptive use, fertility desires) and phlebotomy (October 2011–March 2013). We describe prevalence of effective contraceptive use (i.e., consistent condom use and/or oral contraceptives, injectable hormonal contraception, intrauterine device, female sterilization) in the previous 6 months among sexually active, non-pregnant women (18–40 years). We assessed covariates of contraceptive use using multivariable logistic regression. Results: A total of 362 women (median values: age 30 years, CD4 count 397 cells/mm3, 4.0 years since ART initiation) were included. Among 284 sexually active women, 50% did not desire (another) child, and 51% had a Sero-concordant partner. Forty-five percent (n=127) reported effective contraceptive use, of whom 57% (n=72) used condoms, 42% (n=53) injectable, 12% (n=15) oral contraceptives and 11% (n=14) other effective methods. Dual contraception was reported by 6% (n=8). Only “partnership fertility desire” was independently associated with contraceptive use; women who reported that neither partner desired a child had significantly increased odds of contraceptive use (adjusted odds ratio: 2.40, 95% confidence interval: 1.07–5.35) compared with women in partnerships where at least one partner desired a child. Conclusions: Less than half of sexually active HIV-infected women accessing ART used effective contraception, of which 44% (n=56) relied exclusively on male condoms, highlighting a continued need to expand access to a wider range of longer-acting female controlled contraceptive methods. Association with partnership fertility desire underscores the need to include men in reproductive health programming
Keywords: HIV; Antiretroviral therapy; Family planning; Contraceptive use; Uganda